BANK DATA PROCESSING APPLICATIONS ON UNIVERSITY PROBLEMS - Muhammad Iqdam; Hadiyanto Eko, SSI, MMSi (Jurnal Sistem Informasi, 2005)
Every student in obtaining educational sciences, there is one thing that should theytravel to see the results of the evaluation study that has been obtained previously, thisis a test. This exam is given by the teaching staff in certain times. To organize theexamination of the teaching staff must provide the questions that will be tested. Thisprocess is usually carried about by the teaching staff prior to conducting examinationsto students.Making process about who performed each test enghadapi make the performance lesseffective teachers, because more time is needed for the processing of these matters.For that needed a software that can process data about, with the aim of the workprocess lighten the teaching staff in creating problems when will execute the test.